2008
DOI: 10.1523/jneurosci.4441-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal to Early Postnatal Nicotine Exposure Impairs Central Chemoreception and Modifies Breathing Pattern in Mouse Neonates: A Probable Link to Sudden Infant Death Syndrome

Abstract: Nicotine is a neuroteratogen and is the likely link between maternal cigarette smoking during pregnancy and sudden infant death syndrome (SIDS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
96
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 56 publications
7
96
2
Order By: Relevance
“…68,69 Functional correlates of nicotine exposure include hypoventilation and apnea, as well as blunted chemoreflexes in response to hypoxia. [70][71][72] Studies in human fetal subjects who have been exposed to nicotine have provided a better understanding of the molecular mechanisms underlying the developmental behaviors seen with prenatal nicotine exposure. For example, researchers have found that prenatal cigarette e7 by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from exposure is associated with a decrease in the expression of the genes related to the endogenous opioid system in areas of the brain, the nucleus accumbens, that have been implicated in behavior motivation and mood regulation.…”
Section: Health Consequences Of Exposure To Nicotinementioning
confidence: 99%
“…68,69 Functional correlates of nicotine exposure include hypoventilation and apnea, as well as blunted chemoreflexes in response to hypoxia. [70][71][72] Studies in human fetal subjects who have been exposed to nicotine have provided a better understanding of the molecular mechanisms underlying the developmental behaviors seen with prenatal nicotine exposure. For example, researchers have found that prenatal cigarette e7 by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from exposure is associated with a decrease in the expression of the genes related to the endogenous opioid system in areas of the brain, the nucleus accumbens, that have been implicated in behavior motivation and mood regulation.…”
Section: Health Consequences Of Exposure To Nicotinementioning
confidence: 99%
“…In fact, prenatalperinatal nicotine exposure causes hypoventilation (19,20), increased apnea periods during normoxia in mice and rats (21), reduction of hypercarbia-and hypoxiainduced ventilatory chemoreflexes in mice (19), rats (20,22), and sleeping lambs (23), reduction of autoresuscitation from primary apnea in rats (24), and delays in the hypoxiainduced awakening response in lambs (23). In the serotonergic system, prenatal nicotine increases serotonin 5-HT 1A R binding in the ROb of baboon fetuses (25) as perinatal tobacco exposure does in the cerebral cortex of rhesus monkeys (26).…”
mentioning
confidence: 99%
“…Blunting of ventilatory chemoreflexes in nicotine-exposed mice is due, in part, to a failure in central chemoreception (19,30). We hypothesized that, in mouse neonates, raphe neurons, which express functional nicotinic acetylcholine receptors (31,32), could be targeted by prenatal-perinatal nicotine exposure, affecting their activities, their electrical properties, and their chemosensitivities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some respiratory cells are present at depths of at least 200 mm below the surface, others are within one or two cell diameters of the surface and are stained by bath application of dye. Recent histological studies by one of us (Eugenin et al 2008) has confirmed that there are few glia present in the mouse brainstem at post-natal day 1, which strongly suggests that the cells that are stained and giving signals are certainly neurons and not glia.…”
Section: Discussionmentioning
confidence: 95%